More than an anticoagulant: Do heparins have direct anti-inflammatory effects? - Poterucha, Timothy J.; Libby, Peter; Goldhaber, Samuel Z. (Thrombosis and Haemostasis, 2017)
The heparins, well-known for their anticoagulant properties, may also have anti-inflammatory effects that could contribute to their effectiveness in the treatment of venous thromboembolism and other vascular diseases. This review focuses on the inflammatory pathophysiology that underlies the development of thrombosis and the putative effects of heparin on these pathways. We present evidence supporting the use of heparin for other indications, including autoimmune disease, malignancy, and disseminated intravascular coagulation. These considerations highlight the need for further research to elucidate the mechanisms of the possible pleiotropic effects of the heparins, with a view to advancing treatments based upon heparin derivatives.
Keywords: Heparin; Coagulation; inflammation